A Revised Hippocratic Oath for the Era of Digital Health - Bertalan Meskó; Brennan Spiegel (JMIR Publications, 2022)
Physicians have been taking the Hippocratic Oath for centuries. The Oath contains a set of ethical rules designed to guide physicians through their profession; it articulates a set of true north principles that govern the practice of medicine. The Hippocratic Oath has undergone several revisions, most notably in 1948 by the World Medical Association. However, in an era of rapid change in medicine, we believe it is time to update the Oath with modest but meaningful additions so that it optimally reflects 21st century health care. The rise of digital health has dramatically changed the practice of medicine in a way that could not have been easily predicted at the time Hippocrates outlined his ethical principles of medicine. Digital health is a broad term that encompasses use of digital devices and platforms, including electronic health records, patient-provider portals, mobile health apps, wearable biosensors, artificial intelligence, social media platforms, and medical extended reality, to improve the process and outcomes of health care delivery. These technologies have driven a cultural transformation in the delivery of care. We offer modest suggestions to help prompt discussion and contemplation about the current Oath and its relevancy to our changing times. Our suggestions are not meant to be a definitive set of final recommendations. Rather, we propose new text that bodies such as the World Medical Association might consider integrating into an updated Oath, just as previous changes were adopted to ensure the Oath remains relevant and impactful for all physicians and their patients.